The impact of environmental regulations on the upgrading of the industrial structure: Evidence from China - Haicheng Zhu; Hao Fang; Feilong Hua; Wei Shao; Penghui Cai (Heliyon, 2024)
China's economy has transitioned into a phase of high-quality development, with enhancing its industrial structure becoming a critical objective. We gathered panel data from 30 major provinces in China from 2010 to 2020 and employed the fixed effects model to assess the actual influence of environmental regulations on industrial structure upgrading. Our empirical findings show that the impacts of various environmental regulations on industrial structure upgrading in China are significantly different. Mandatory environmental regulation demonstrates an inverted U-shaped nonlinear correlation with the upgrading level of the entire industrial structure. When the intensity of this regulation is low, it significantly accelerates industrial structure upgrading. As the intensity of this regulation rises, its effect on industrial structure upgrading is inhibitory. In contrast, induced environmental regulation exhibits a nonlinear U-shaped relationship with industrial structure upgrading and shows a nonlinear change trend of first decreasing and then rising. When the intensity of induced environmental regulation reaches a certain critical point and continues to increase, it will change from a negative influence on the upgrading of the industrial structure to a promoting effect. The further discussion of threshold regression and the robustness test also led to similar conclusions. The above research is conducive to the Chinese government's rational use of environmental regulation tools to promote industrial structure upgrading. It is also beneficial to developing countries, allowing them to learn from China's experience to improve the effectiveness of environmental regulation and boost their industrial development.